PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS PENDEKATAN SAINTIFIK PADA MATERI TRIGONOMETRI - Fadila El Husna (Departemen Matematika, 2021)
This study aims to develop modules on trigonometry lessons based on scientific approach for students of class X SMA/MA that are valid and practical. The research was conducted at SMA Negeri 1 Padang Panjang, Padang Panjang in class X MIPA 4. The type of research is Research and Development with the Plomp model which goes through two stages, namely preliminary research and prototyping phase. The preliminary research stage consists of four analyzes, namely needs analysis, student analysis, curriculum analysis and concept analysis. The prototyping phase consists of prototype 1, prototype 2, prototype 3 and prortype 4. The results showed that the scientific approach-based module can be categorized as valid and practical. Based on the results of the validation by the validator, the scientific approach-based module meets the very valid category with a validity level of 85.28%. Then based on research, scientific approach-based modules can be categorized as very practical with a practicality level of 87.64% by students. Keywords Module, Scientific Approach, Valid, Practical